An investigation on the influence of friends in information cascade - experimental evidence in laboratories. - Lim, Wei Jie. (2013)
This paper examines the impact of relationships on the occurrence of cascade outcome by conducting the ball and urn experiment on the Friend treatment and Stranger treatment under laboratory conditions. By implementing the standard BHW model which argues information cascading using Bayes’ rule and by performing multinomial logistic model, it was concluded that there is a significant increase in cascade outcome moving from the Stranger treatment to the Friend treatment. With the presence of trust among friends, it could lead to a cascade of influence and hence, the higher probability of cascade formation. An extension of the study is to perform a similar experiment by using an investment setting. The result shows that there is no treatment effect under an investment situation and this finding was proven insignificant by the multinomial logistic model. Possible explanations may be due to the increase in uncertainty and randomness in one’s private signals and the belief that strangers may have additional information which is not accessible to friends within similar network surroundings.